Tiger hate to lose: read it yourself :disnep - Stevenson, Peter (Ladybird London, 2004)
"Tiger Hates to Lose" follows a competitive tiger who struggles with losing games and competitions. As he faces challenges and defeats, he learns important lessons about sportsmanship, teamwork, and the value of trying your best. Through his journey, Tiger discovers that it's not just about winning, but also about having fun and supporting friends, ultimately growing as a player and a friend.